Evaluation of the wound healing activity of the formulated ointment using extracted curcumin from Curcuma longa L. (Fam. Zingiberaceae) powder among diabetes-induced Sprague-Dawley rats - Alvarez, Jaslyn P.; Basco, Cornellie M.; Pascual, Allan Christopher DG.; Balotro, Bienvenido S. (Manila: Department of Industrial Pharmacy, College of Pharmacy, University of the Philippines Manila, 2017)
The primary purpose of this study is to evaluate the wound-healing activity of the formulated ointment of curcumin extracted from C. longa powder among diabetes-induced male Sprague-Dawley rats, in terms of percentage wound closure, period of epithelialization, percentage of scar formed, and histopathological analysis. This study was conducted in the University of the Philippines Manila College of Pharmacy. Thirty male Sprague-Dawley rats were subjected to chemical induction of alloxan monohydrate with 110 mg/kg dose. Diabetic rats were randomized and distributed into three treatment groups namely 1%, 5%, and 10% curcumin extract in formulated ointment, and two control groups namely positive control (Mupirocin) and negative control (white petrolatum and beeswax). Wound areas were measured using a standardized set-up of a constant fixture of 15-cm perpendicular distance from an iPhone 6 camera. Photographs of excisional wound areas were analyzed by ImageJ software. Histopathological analysis was done to evaluate inflammatory cell infiltration, neovascularization, fibroblast ingrowth, and collagen formation. The results of the wound healing parameters were analyzed using Shapiro-Wilk test, Bartlett?s test, One-way ANOVA, Scheffe test, Kruskal-Wallis test and Dunn test. The statistical software used were Stata/IC version 13 and IBM SPSS Statistics version 23.
Results showed that 10% curcumin ointment exhibited better percentage wound closure and period of epithelialization, and comparable histopathological analysis against Mupirocin (positive control). Cost analysis also showed that the formulated ointment, with a cost of Php 99.84, was more affordable than the xiv existing brands of Mupirocin. With these, it is therefore concluded that 10% curcumin ointment is a low cost and an effective agent for wound healing.
It is recommended to consider other hydrophobic ointment bases and to conduct both accelerated and real time stability studies. The use of cell lines in doing the wound healing assay is also recommended. Another recommendation is to perform a skin irritation test which may either be done through OECD 439 or Reconstructed Human Epidermis Test.
Available to the general public.
Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines Manila, June 2017.
Keywords: Wound Healing; Ointments; Zingiberaceae